2011
DOI: 10.1126/science.1201538
|View full text |Cite
|
Sign up to set email alerts
|

Positive Supercoiling of Mitotic DNA Drives Decatenation by Topoisomerase II in Eukaryotes

Abstract: DNA topoisomerase II completely removes DNA intertwining, or catenation, between sister chromatids before they are segregated during cell division. How this occurs throughout the genome is poorly understood. We demonstrate that in yeast, centromeric plasmids undergo a dramatic change in their topology as the cells pass through mitosis. This change is characterized by positive supercoiling of the DNA and requires mitotic spindles and the condensin factor Smc2. When mitotic positive supercoiling occurs on decate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
186
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(196 citation statements)
references
References 19 publications
9
186
0
1
Order By: Relevance
“…Cdc14 mediates a shutdown of rDNA transcription, facilitating the loading of the Smc2 condensin and hence the condensation of the cluster (Yoshida et al , 2002; D'Amours et al , 2004; Sullivan et al , 2004, 14; Machín et al , 2006; Clemente‐Blanco et al , 2009). In addition, topoisomerase II (Top2), which decatenates the intertwining structures that appear between SCs during replication, is also required for rDNA segregation to proceed (Sullivan et al , 2004; D'Ambrosio et al , 2008; Baxter et al , 2011; Leonard et al , 2015). We investigated the influence of those factors on the 3D structure of the rDNA locus during anaphase (Figs 5A and EV5; Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
“…Cdc14 mediates a shutdown of rDNA transcription, facilitating the loading of the Smc2 condensin and hence the condensation of the cluster (Yoshida et al , 2002; D'Amours et al , 2004; Sullivan et al , 2004, 14; Machín et al , 2006; Clemente‐Blanco et al , 2009). In addition, topoisomerase II (Top2), which decatenates the intertwining structures that appear between SCs during replication, is also required for rDNA segregation to proceed (Sullivan et al , 2004; D'Ambrosio et al , 2008; Baxter et al , 2011; Leonard et al , 2015). We investigated the influence of those factors on the 3D structure of the rDNA locus during anaphase (Figs 5A and EV5; Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
“…Since conditional genetic ablation of Top2 prevents decatenation, the number of DNA catenanes formed on plasmid replicons during DNA replication in yeast cells can be directly assayed. These assays have shown that fork rotation on yeast episomal plasmids is relatively infrequent and generally limited to the regions around converging forks in a similar manner to SV40 or E. coli [31,32].…”
Section: Topoisomerase Action and Dna Catenationmentioning
confidence: 99%
“…These observations would be consistent with the alternative model where condensin action leads to DNA supercoiling of the mitotic chromosome fibres. This model is derived from studies that have shown that condensin complexes drive the generation of positive supercoiling on plasmids in vitro following activation by mitotic kinases [76,77] and are required for mitotic supercoiling of plasmids in vivo in a manner that drives decatenation of sister chromatids [32]. Decatenation is presumably driven by the intra-chromosomal coiling exposing interchromosomal linkages to the outside of chromatid masses ( Figure 5B) in a manner analogous to that proposed for supercoiling of chromatids in E. coli ( Figure 5A).…”
Section: Eukaryotic Chromosome Compactionmentioning
confidence: 99%
“…A recent study in S. cerevisiae has provided evidence that condensin is indeed responsible for accumulation of positive supercoils on catenated sister DNAs in vivo under the condition in which topo II is depleted (Baxter et al 2011). Remarkably, when tested in vitro, catenated plas- mids with positive supercoils are more susceptible to topo II-mediated decatenation than those with no supercoils (Fig.…”
Section: Supercoiling and Decatenating Dsdnamentioning
confidence: 99%